Pemanfanfaatan Media Gambar Untuk Meningkatkan Hasil Belajar Mata Pelajaran IPS Sejarah Pada Siswa SMP Negeri 13 Kota Ternate - Zulkifli Zulkifli; Leny MS. Tomagola (Peneliti.net, 2023)
IPS subjects are very important subjects and provide knowledge for students, so techniques are needed in presenting the material so that the objectives of learning IPS at SMP Negeri 13 Kota Ternate can be achieved properly. For this reason, media images have quite an important meaning in teaching and learning activities such as historical sites in historical social studies subjects that are conveyed by the teacher to students, which can be assisted by the media as an intermediary so that the material conveyed by the teacher, students can understand. well besides that, it can improve student learning outcomes. Because Social Sciences (IPS) is one of the subjects at the junior high school level, which is developed in an integrated manner by taking essential concepts from the Social Sciences and Humanities, and social studies subjects are a combination of various scientific disciplines, such as economics. , history, geography, and sociology which are arranged in a systematic and integrated manner which then becomes a scientific discipline that cannot be broken down anymore because it has been integrated into social science. So with media images, social studies teacher goals can be achieved well because the material delivered by the teacher, students do not feel bored and bored besides that it can improve learning outcomes